ANALISIS KEBERHASILAN PELATIHAN MENGGUNAKAN METODE EMPLOYEE NET PROMOTER SCORE DAN MODEL KIRKPATRICK - Aisjah, Siti; Almira, Yorina Huwaida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research aims to analyze trainings’ success using Employee Net Promoter Score Method and Kirkpatrick Model. As this study attempts to conclude research phenomena that are disclosed using research reports, it is considered as descriptive research. Using saturated sampling, all eight employees of PT. XYZ who have joined sales negotiation trainings were selected as the sample. Based on the descriptive statistical analysis, the Employee Net Promoter Score is in the high category. According to Kirkpatrick Model analysis, the relevance of the training programs with the real job is in the outstanding category, the understandability of the training material is in the outstanding category, the applicability of the training materials to the real job is in the outstanding category, facilitators’ attractiveness in running the program is in the outstanding category, and the understandability of facilitators in delivering the material is in the outstanding category. Based on the scores above, it can be concluded that the trainings conducted by PT. XYZ is successful.